Extracorporeal Membrane Oxygenation in Severe Acute Respiratory Distress Syndrome Caused by Chlamydia psittaci: A Case Report and Review of the Literature - Wang, Lu; Shi, Zhaokun; Chen, Wei; Du, Xianjin; Zhan, Liying (Frontiers in Medicine, 2021)
Background: Infection of Chlamydia psittaci (C. psittaci) could lead to serious clinical manifestations in humans, including severe pneumonia with rapid progression, adult respiratory distress syndrome (ARDS), sepsis, multiple organ dysfunction syndromes (MODS), and probably death. Implementation of extracorporeal membrane oxygenation (ECMO) in the patient with severe ARDS gives a promising new method for recovery. Case Presentation: We report our successful use of venovenous (VV) ECMO in a 48-year-old man who manifested with severe respiratory distress syndrome, acute kidney injury, and septic shock caused by a diagnosis of pneumonia. After the combination of therapy including anti-infection, mechanical ventilation, and continuous renal replacement therapy (CRRT), acute inflammatory syndrome developed. However, his respiratory status rapidly deteriorated. Then, venoarterial (VA)-ECMO support was placed on the patient as suddenly slowing of the heart rate. Harlequin (North-South) syndrome occurred after ECMO initiation. A series of the process could not relieve hypoxia in the upper body. At last, transition to VV-ECMO improved hypoxia. The duration of VV-ECMO was 7 days and the mechanical ventilation was weaned on the next day. On the day of ECMO weaning, nanopore targeted sequencing (NTS) of bronchoalveolar lavage fluid (BALF) reported the presence of C. psittaci. After 19 days of critical systemic rehabilitation and combination therapy, the patient fully recovered from C. psittaci. Conclusion: This is the first reported case of the patient receiving ECMO for C. psittaci pneumonia. ECMO puts the lungs on temporary rest, promotes the recovery of pulmonary function, and also wins time for finding the pathogens, which is crucial in the treatment of rare pathogens.